ANALISIS PENGUKURAN USABILITY MENGGUNAKAN METODE USE QUESTIONNAIRE PADA APLIKASI SHOPEE INDONESIA - Erina Oktariana Nurazizah (2021)
Along with the development of the Shopee application, many users also complain about the shortcomings of the Shopee application features itself. To ensure user satisfaction, the authors conducted research on usability calculations on the Shopee application. Usability calculations are taken from the subjective point of view of Shopee application users. In this study, author decide to use USE Questionnaire method using a questionnaire consisting of 30 statements representing 4 USE Questionnaire parameters, such as Usefulness, Ease of Use, Ease of Learning and User Satisfaction. In this study, the author will also prove several hypotheses in the form of the influence of the independent variable of the USE Questionnaire method with the dependent variable. The questionnaire then distributed to Shopee application users. From this data, calculations can then be made according to the 3 parameters of the USE Questionnaire, namely Usefulness, Ease of Use and Ease of Learning on the User Satisfaction parameter. The data obtained through the questionnaire, then a feasibility test will be carried out in the form of validity and reliability, descriptive test, classical assumption test in the form of normality test, hypothesis testing in the form of multiple linear regression analysis, partial significance test (t test), simultaneous significance test (f test) and the coefficient of determination (R2 square). In each test carried out, the answers to the following questions will be obtained, whether the data is reliable and valid, what is the category of the usefulness of the Shopee application, is the data normally distributed, whether the user satisfaction variable has a positive effect on the other 3 USE Questionnaire method variables and how much the magnitude of the influence, and whether the hypothesis is accepted or rejected and vice versa. The results of the analysis show that the measurement of the usability of the USE Questionnaire variable in the Shopee application is 82.88%, which means the usability level of the Shopee Indonesia application is "high". Also for the influence value of 3 parameters USE Questionnaire, such as Usefulness, Ease of Use and Ease of Learning on the User Satisfaction parameter is 61.6%, which means the influence of these 3 parameters is declared "strong/high". Based on the tests carried out, it can also be concluded that all hypotheses regarding the influence of the independent variables of the USE Questionnaire method with the dependent variable are entirely accepted. By doing this research, the author hopes that the Shopee application, especially Shopee Indonesia, can improve the quality of the application according to the needs of users based on the analysis that has been done.